Kinetic Characterization and Inhibitor Screening of Pyruvate Kinase I From Babesia microti - An, Xiaomeng; Yu, Long; Wang, Sen; Ao, Yangsiqi; Zhan, Xueyan; Liu, Qin; Zhao, Yangnan; Li, Muxiao; Shu, Xiang; Li, Fangjie; He, Lan; Zhao, Junlong (Frontiers in Microbiology, 2021)
The apicomplexan Babesia microti is the main pathogenic parasites causing human babesiosis. It is one of the most widely distributed ticks-borne diseases in human. Pyruvate kinase (PyK) plays a central metabolic regulatory role in most living organisms, which catalyzes the essentially irreversible step in glycolysis converting phosphoenolpyruvate (PEP) to pyruvate. Consequently， PyK is recognized as an attractive therapeutic target in cancer and human pathogens, like apicomplexans. In this study, we cloned, expressed and purified B. microti pyruvate kinase Ⅰ (BmPyKⅠ). Western blot illustrated that anti-BmPyKⅠ antibody specifically recognized the native BmPyKⅠ protein in lysates of B. microti with a 56 kDa band which is consistent with the predicted size. In addition, the enzymatic activity of the purified recombinant PyKⅠ (rPyKⅠ) was tested under a range of pH values. The results showed that the maximum catalytic activity at pH 7.0. The saturation curves for substrates demonstrated that the Km value for PEP was 0.66 ± 0.12 mM and the Km value for ADP was 0.14 ± 0.03 mM. We further investigated the effect of 13 compounds on PyKⅠ. Kinetic study indicated that 6 inhibitors (tannic acid, shikonin, apigenin, PKM2 inhibitor，rosiglitazone and pioglitazone） could significantly inhibit the catalytic activity of PyKⅠ. Tannic acid is the most efficient inhibition with a IC50 value 0.49 μM. On the other hand, four inhibitors (tannic acid, apigenin, shikonin and PKM2inhibitor) can significantly decreased the growth of B. microti in vitro culture with IC50 of 0.77 μM, 2.10 μM, 1.73 μM and 1.15 μM, respectively. In conclusion, the present study will provide a theoretical basis for the design and development of new anti-Babesia drugs.